MEMBANGUN QUALITY TIME ORANG TUA DENGAN ANAK USIA 4-6 TAHUN DI KOTA MALANG - Damayanti, Ervina; Elvira, Melly (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Quality time is time spent together with full focus on children, creating emotional bonds, and strengthening family relationships. This involves activities that not only fill time, but also add value to the child's development and create positive memories. This research aims to describe the quality time of parents with children aged 4-6 years in Malang City. The research method uses a quantitative approach with a survey research type with a sample of 253 parents in Malang City who have children aged 4-6 years. Data collection uses questionnaire techniques. Data analysis uses descriptive data analysis. The results of this study show that the majority of parents spend quality time with their children well. With an average percentage of 86% which is included in the